Fulfillment of Children's Constitutional Rights within the Framework of a Child-Friendly City (CFC) in Pekalongan - Kamalludin, Iqbal; Wibowo, Mohamad Agung (Asian Journal of Law and Humanity, 2024)
Pekalongan Regency is one of the regions that has held the title of child-friendly City in the Central Java Province region since 2015, the primary criteria for which this award was directly given by the Ministry of Women's Empowerment and Child Protection of the Republic of Indonesia in Semarang, after carrying out an intensive assessment in 2014 In 2021, Pekalongan Regency succeeded in winning the Child Friendly City (CFC) award again with intermediate criteria and won the Parahita Ekapraya Award (APE) five times. Pekalongan Regency has received the Child Friendly City (CFC) awards with average criteria from 2015, 2017, 2018, 2019, 2021, 2022 and 2023. However, the high number of children's rights that have not been fulfilled, stunting, children not in school (ATS), Ownership of children's birth certificates in Pekalongan Regency is still said to be quite high. This research uses empirical juridical research using a qualitative approach. The data obtained are primary data and secondary data. Meanwhile, data collection techniques emphasize observation, interviews and documentation. The results of this research have not been implemented well because it has not run ideally and not all related fields or departments can be equal in terms of fulfilling children's rights. Several departments that carried out research included the Education Service, Health Service, Population and Civil Registration Service, Women's Empowerment and Child Protection Service and the Regional Development Planning Agency. In this case, the fulfillment of children's constitutional rights within the Child Friendly Regency (CFC) framework in the Regency Pekalongan can run ideally if the three elements of the Welfare State theory are fulfilled.